Emerging Role of Exosomes in Tuberculosis: From Immunity Regulations to Vaccine and Immunotherapy - Sun, Yin-Fu; Pi, Jiang; Xu, Jun-Fa (Frontiers in Immunology, 2021)
Exosomes are cell-derived nanovesicles carrying protein, lipid, and nucleic acid for secreting cells, and act as significant signal transport vectors for cell-cell communication and immune modulation. Immune-cell-derived exosomes have been found to contain molecules involved in immunological pathways, such as MHCII, cytokines, and pathogenic antigens. Tuberculosis (TB), caused by mycobacterium tuberculosis (MTB), remains one of the most fatal infectious diseases. The pathogen for tuberculosis escapes the immune defense and continues to replicate despite rigorous and complicate host cell mechanisms. The infected-cell-derived exosomes under this circumstance are found to trigger different immune responses, such as inflammation, antigen presentation, and activate subsequent pathways, highlighting the critical role of exosomes in anti-MTB immune response. Additionally, as a novel kind of delivery system, exosomes show potential in developing new vaccination and treatment of tuberculosis. We here summarize recent research progress regarding exosomes in the immune environment during MTB infection, and further discuss the potential of exosomes as delivery system for novel anti-MTB vaccines and therapies.